Saving the Sun Dragon : Dragon Masters #2 - West, Tracey, 1965-; Howells, Graham (New York, NY : Scholastic Inc., 2014)
The dark magic the dragons encountered in their first adventure has made Ana's sun dragon, Kepri, sick and Drake's earth dragon, Worm, teleports the himself, Kepri, and the four young dragon masters far away from the castle in search of a cure--but the threat of the dark magic still remains.
Appeals to 1st-3rd graders.
Reading level grade 2.
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Dragons -- Fiction; Wizards -- Fiction; Magic -- Fiction